Analysis of tenodesis techniques for treatment of scapholunate instability using the finite element method. (27th July 2017) - Alonso Rasgado, Teresa; Zhang, Qinghang; Jimenez Cruz, David; Bailey, Colin; Pinder, Elizabeth; Mandaleson, Avanthi; Talwalkar, Sumedh
Abstract: Chronic scapholunate ligament (SL) injury is a common disorder affecting the wrist. Despite advances in surgical techniques used to treat this injury, SL gap re‐emergence may occur postoperatively. This paper presents an investigation into the performance of the Corella, schapolunate axis (SLAM), and modified Brunelli tenodesis (MBT) surgical reconstruction techniques used to treat scapholunate instability. Finite element (FE) models were used to undertake virtual surgery, and the resulting scapholunate (SL) gap and angle obtained using the 3 techniques were compared. The Corella technique was found to achieve the SL gap and angle closest to the intact (ligament) wrist, restoring SL gap and angle to within 5.6% and 0.6%, respectively. The MBT method resulted in an SL gap least close to the intact. The results of our study indicate that the contribution of volar scapholunate interosseous ligament to scapholunate stability could be important. Abstract : Chronic scapholunate (SL) ligament injuries are difficult to treat and can lead to wrist dysfunction. Virtual tenodesis surgery was undertaken in 3D finite element models to obtain the SL gap and angle resulting from the 3 reconstruction techniques. The Corella technique was found to achieve the SL gap and angle closest to the intact, restoring SL gap and angle to within 5.6% and 0.6%, respectively.